THE EFFECT OF USING TIKTOK APPLICATION ON STUDENTS’ VOCABULARY MASTERY AT SENIOR HIGH SCHOOL STUDENT - Nadia Nainggolan; Sondang Manik (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2024)
The purpose of this study is to find out the effect of applying TikTok application in vocabulary learning. This uses a quantitative study, which is a quasi-experimental method. Data from this study are collected and obtained through tests and observation. The subjects of this study are X-IPA with samples X-IPA 8 as the experimental group and X-IPA 5 as the control group, totaling 74 students who were selected by random technique. Tests are conducted by pre-test and post-test, then observation by observing and recording samples. The result of the study shows that using the TikTok application significantly affects students’ vocabulary mastery. This can be seen from some facts, such as 1) the Mean post-test of experimental after treatment is 83,03, while control is 58,92, 2) the Standard deviation post-test of experimental after treatment is 9036,97, while control is 2772,76, 3) T-count after treatment is 5,81, meanwhile t-table level 0,05 is 1,666. Thus 5,81 > 1,666). This study shows that TikTok applications have a good influence on vocabulary learning.